The researchers we need (in the Health System of Cienfuegos) - Alfredo Darío Espinosa Brito; Alfredo Alberto Espinosa Roca (Medisur)
The importance of science and technique in the Cuban and Cienfuegos Health System is addressed, as well as the need for new researchers and new scientific results, to achieve the desired prosperous and sustainable development in our country. The main characteristics of the needed researchers are suggested and five groups are proposed, with emphasis on those who work on scientific problems related to the individual clinical care, the organization of health services and the actions of Public Health in the population, as well as in the formation of human capital. Emphasis is placed on those who, having previous professional experience enough time, know how to turn a clinical or public health problem (care, teaching, or management) into a research problem and solve it with an appropriate methodology. Emphasis is placed on the results implementation and their appropriate evaluation by researchers and authorities. It is necessary to consider that the current challenge is to reconcile new training strategies offered, with the available potential and the real research needs. Although the main interest of this work is directed to the Provincial Health System of Cienfuegos, some of the ideas expressed here could be useful in other contexts of the country, on the basis of taking into account the particular objectives and characteristics of each place.